2021
DOI: 10.1001/jamanetworkopen.2021.31129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cervical Cancer Screening Uptake and Adherence Among Women Without Human Papillomavirus Vaccination in the US

Abstract: to-date status for women aged 21 to 29 y was established by considering whether they had received a Papanicolaou test within the past 3 years. Up-to-date screening for women aged 30 to 39 y was either having a Papanicolaou test within the past 3 years or having a Papanicolaou test with an HPV cotest within the past 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…Human papillomavirus vaccination was even less likely to be a reason for not being up to date on screening among those aged 30 to 65 years because most women in that age group were not generally eligible to receive the HPV vaccine, and coverage among those who were eligible to receive the vaccine was fairly low. In addition, a previous study found that women aged 21 to 39 years who did not receive an HPV vaccine were significantly more likely to be overdue for cervical cancer screening compared with those who received an HPV vaccine, further increasing their risk of cervical cancer …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Human papillomavirus vaccination was even less likely to be a reason for not being up to date on screening among those aged 30 to 65 years because most women in that age group were not generally eligible to receive the HPV vaccine, and coverage among those who were eligible to receive the vaccine was fairly low. In addition, a previous study found that women aged 21 to 39 years who did not receive an HPV vaccine were significantly more likely to be overdue for cervical cancer screening compared with those who received an HPV vaccine, further increasing their risk of cervical cancer …”
Section: Discussionmentioning
confidence: 77%
“…In addition, a previous study found that women aged 21 to 39 years who did not receive an HPV vaccine were significantly more likely to be overdue for cervical cancer screening compared with those who received an HPV vaccine, further increasing their risk of cervical cancer. 18 The primary reason for not having up-to-date screening among all groups in all years was not knowing that screening was needed. The fact that this reason increased over time across most sociodemographic groups suggests a need for interventions targeting screening awareness for all women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are consistent with previous studies in young women. [17][18][19] In a Canadian study 17 the age-adjusted screening participation (aged 18 to 21) was 13.0% for vaccinated versus 11.4% for unvaccinated women (vaccination coverage at least 2 doses: 40.8%). In a Danish study, 20 the screening participation (aged 23) was 61.4% for vaccinated women versus 39.0% for unvaccinated women (vaccination coverage at least 1 dose: 91.2%).…”
Section: Discussionmentioning
confidence: 99%
“…In one study specific to women who had not received the human papillomavirus (HPV) vaccine in 2019, 32.2% of women aged 21-29 years had never been screened. 11 Also in 2019, women aged 21-29 years had a 29% rate of overdue screening. 12 We are not seeing an improvement in screening uptake, with the proportion of women of all ages without up-to-date screening increasing significantly from 2005 to 2019 (from 14.4% to 23.0%; p < .001).…”
mentioning
confidence: 99%
“…Although screening numbers in the United States are better than those in India, they are still unacceptably low. In one study specific to women who had not received the human papillomavirus (HPV) vaccine in 2019, 32.2% of women aged 21–29 years had never been screened 11 . Also in 2019, women aged 21–29 years had a 29% rate of overdue screening 12 .…”
mentioning
confidence: 99%